Collectors of Daily Life: The Literary Journalist, the Anthropologist, and Their Fieldwork - Guimarães de Carvalho, Beatriz; de Almeida Evangelista, Rafael (Brazilian journalism research, 2018)
Literary journalists and anthropologists conduct their fieldwork with similar tools and goals. Both use listening and observation to establish contact with the Other - the group being studied - and therefore identify, understand and interpret daily interactions and scenes. In spite of the similarities, their conduct in the field suffers interference due to the certain particularities of each one of them: production conditions, professional relations, social roles, methodological principles, professional ethics and the commitment to the final product – scientific research or literary reporting. In this article, we put forth a theoretical reflection about the similarities and contrasts between the fieldwork of literary journalists and anthropologists. At the same time, we reflect on what characterizes each of these professional researchers and their respective disciplines. For this purpose, we explore authors such as Harrington (2003), Martinez (2008; 2017), Lago (2010), Brandão (2007), Travancas (2002; 2014) and Gillespie (2012). Jornalistas literários e antropólogos vão a campo com ferramentas e buscas em comum. Ambos usam a escuta e a observação para estabelecer contato com o Outro – o grupo pesquisado – e, assim, identificar, compreender e interpretar relações e cenas cotidianas. Apesar das proximidades, a conduta de cada um deles em campo sofre interferências devido a particularidades carregadas na bagagem: condições de produção, vínculos de trabalho, papéis sociais, princípios metodológicos, ética profissional e compromisso com o produto final – a pesquisa científica ou a reportagem literária. Neste artigo, levantamos uma reflexão teórica acerca das conexões e contrastes entre o trabalho de campo praticado pelo jornalista literário e pelo antropólogo. Ao mesmo tempo, buscamos refletir sobre o que caracteriza cada um desses profissionais-pesquisadores e suas respectivas disciplinas. Para tal, são explorados autores como Harrington (2003), Martinez (2008; 2017), Lago (2010), Brandão (2007), Travancas (2002; 2014) e Gillespie (2012). Periodistas literarios y antropólogos van al campo con herramientas y búsquedas en común. Ambos usan la escucha y la observación para establecer contacto con el Otro - el grupo investigado - y así identificar, comprender e interpretar relaciones y escenas cotidianas. A pesar de las similitudes, la conducta de ambos en campo sufre interferencias debido a particularidades cargadas en el equipaje: las condiciones de producción, los vínculos de trabajo, los papeles sociales, los principios metodológicos, la ética profesional y el compromiso con el producto final - la investigación científica o el reportaje literario. En este artículo, levantamos una reflexión teórica acerca de las conexiones y contrastes entre el trabajo de campo practicado por el periodista literario y el antropólogo. Al mismo tiempo, buscamos reflexionar sobre lo que caracteriza cada uno de esos profesionales-investigadores y sus respectivas disciplinas. Con este objectivo, se exploran autores como Harrington (2003), Martinez (2008; 2017), Lago (2010), Brandão (2007), Travancas (2002; 2014) y Gillespie (2012).